2021
DOI: 10.1007/s00394-021-02685-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulse consumption improves indices of glycemic control in adults with and without type 2 diabetes: a systematic review and meta-analysis of acute and long-term randomized controlled trials

Abstract: Purpose Findings from randomized controlled trials (RCTs) evaluating the effect of pulse intake on glycemic control are inconsistent and conclusive evidence is lacking. The aim of this study was to systematically review the impact of pulse consumption on post-prandial and long-term glycemic control in adults with and without type 2 diabetes (T2D). Methods Databases were searched for RCTs, reporting outcomes of post-prandial and long-term interventions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Increased consumption of carbohydrates in the HND did not increase any of the glucose variables and kept the mean glucose lower than the diet with less carbohydrates. The HND had the additional bene t of including carbohydrates from legumes, which have been bene cial for glycemic control in type 2 diabetic populations (35). Although some evidence suggest that low carbohydrate diet could be more disadvantageous for the insulin resistance and blood lipid concentrations compared to high carbohydrate diet (15,20), our results did not adversely affect this in the short term.…”
Section: Discussionmentioning
confidence: 56%
“…Increased consumption of carbohydrates in the HND did not increase any of the glucose variables and kept the mean glucose lower than the diet with less carbohydrates. The HND had the additional bene t of including carbohydrates from legumes, which have been bene cial for glycemic control in type 2 diabetic populations (35). Although some evidence suggest that low carbohydrate diet could be more disadvantageous for the insulin resistance and blood lipid concentrations compared to high carbohydrate diet (15,20), our results did not adversely affect this in the short term.…”
Section: Discussionmentioning
confidence: 56%
“…A cross-sectional study examining the effects of different proportions of carbohydrates at breakfast on postprandial glucose fluctuations in IGT (N = 55) and normal glucose tolerance (NGT) individuals (N = 78), using continuous glucose monitoring, recorded breakfast meals according to the proportion of carbohydrates into low (<45%), medium (45% to 65%) and high carbohydrates (>65%), and reported a gradual increase in postprandial glucose fluctuations with increasing proportions of carbohydrates in breakfast, higher postprandial glucose excursions, higher postprandial glucose spikes, and longer time period in which glucose levels decreased to baseline in subjects with IGT compared to NGT individuals; this study concluded that in IGT a high-carbohydrate meal at breakfast should be avoided and a low carbohydrate meal should be recommended instead [84]. Carbohydrate-rich foods that may be more effective in ameliorating postprandial hyperglycemia and IR include legumes/pulses [85][86][87], whole grains [88][89][90][91], and pasta [92]. In 2017, the American Diabetes Association (ADA) proposed consuming the following foods for preventing T2DM along with weight loss: whole grain cereal products, nuts, yogurt, coffee and tea and limit consumption of red meat and sodas containing sugar [93].…”
Section: Effects Of Macronutrients In Foods and Meals On Postprandial...mentioning
confidence: 81%
“…The increasing protein content of food products that have a traditionally low protein content can cause a greater increase in the postprandial levels of anorexigenic peptides released in the gut in response to food ingestion [ 21 ]. Increased legume consumption contributes to higher weight loss in humans with overweight/obesity, along with other beneficial impacts on health [ 28 , 29 , 30 , 31 ]. The exploitation of legume and seed flours for substitution of refined white wheat flour and the development of novel functional foods with lower GI and higher satiety potential can be an interesting new prospect in the food industry.…”
Section: Discussionmentioning
confidence: 99%